2018
DOI: 10.1371/journal.ppat.1007035
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression by ApiAP2 factors is central to chronic toxoplasmosis

Abstract: Tachyzoite to bradyzoite development in Toxoplasma is marked by major changes in gene expression resulting in a parasite that expresses a new repertoire of surface antigens hidden inside a modified parasitophorous vacuole called the tissue cyst. The factors that control this important life cycle transition are not well understood. Here we describe an important transcriptional repressor mechanism controlling bradyzoite differentiation that operates in the tachyzoite stage. The ApiAP2 factor, AP2IV-4, is a nucle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 63 publications
(130 reference statements)
2
69
0
Order By: Relevance
“…Neurons are the primary target cells for Toxoplasma cyst formation within distal neuronal processes (40,41). Bradyzoite differentiation is triggered by changes in nutrition or cellular conditions (42)(43)(44), which drives the transcriptional program that leads to the production of bradyzoite-stage proteins (45,46) and the formation of the cyst wall and cyst structure (32). The cyst wall is a protective structure that safely encloses bradyzoites until their transmission to a new host after oral ingestion of cysts (14).…”
Section: Discussionmentioning
confidence: 99%
“…Neurons are the primary target cells for Toxoplasma cyst formation within distal neuronal processes (40,41). Bradyzoite differentiation is triggered by changes in nutrition or cellular conditions (42)(43)(44), which drives the transcriptional program that leads to the production of bradyzoite-stage proteins (45,46) and the formation of the cyst wall and cyst structure (32). The cyst wall is a protective structure that safely encloses bradyzoites until their transmission to a new host after oral ingestion of cysts (14).…”
Section: Discussionmentioning
confidence: 99%
“…Apicomplexan genomes encode a family of putative transcription factors that are characterized by the possession of one or more DNA binding AP2 domains [16]. ApiAP2 transcription factors were shown to control expression profiles during T. gondii differentiation [17][18][19]. ApiAP2s were also shown to cooperatively control the expression of virulence factors [20,21] in T. gondii indicating that this family of transcription factors may control cell cycle dependent expression profiles as also suggested for P. berghei [22].…”
Section: Introductionmentioning
confidence: 67%
“…Interestingly, much like other genes directly regulated by TgAP2IX-5 ( Figure 4E), these genes showed an expression peak during the late S phase ( Figure S9B). TgAP2IV-4, a known repressor of developmentally regulated genes, is expressed during the S/M phase [18]. These data suggest that TgAP2IX-5 directly activates other TF during the S phase that may in turn control the late S and M expression program.…”
Section: Tgap2ix-5 Impacts the Expression Of Cell-cycle Regulated Genesmentioning
confidence: 77%
See 1 more Smart Citation
“…Other studies have implicated AP2s in regulating a developmental transition 16 . Radke et al 17 recently characterized a T. gondii AP2 and showed that this molecule acts as a repressor of bradyzoite development. Our results showed that egress assay was partially affected by parasite proliferation (Fig 4B).…”
Section: Discussionmentioning
confidence: 99%